Comparative analysis of the mast cell density in normal oral mucosa, actinic cheilitis and lip squamous cell carcinoma - Gomes,Ana Paula Neutzling (2008)
Previous studies have shown that the number of mast cells is increased in ultraviolet (UV) irradiated skin and in neoplasias. Actinic cheilitis (AC) is a lesion caused by excessive exposure to sunlight that can transform into lip squamous cell carcinoma. The aim of this study was to compare the number of mast cells in 4 groups: NOM = normal oral mucosa (n=6); MDAC = mild dysplasia in actinic cheilitis (n=13); SDAC = severe dysplasia in actinic cheilitis (n=13); and LSCC = lip squamous cell carcinoma (n=15). The sections were stained by histochemical technique of blue toluidine and visual counting was performed with the aid of a reticulum coupled to the microscope ocular. A calibrated observer performed the count in 5 fields by case at ×400 magnification. The largest mean number of mast cells per group was observed in LSCC (40.1), followed by MDAC (30.5), SDAC (28.6) and NOM (12.2). There were significant differences between NOM and MDAC (p<0.05) and between NOM and LSCC (p<0.05). The increased density of mast cells observed in AC and in LSCC compared to NOM suggests a role for the mast cells in the development of these lesions.